Study Experimental the Effect of Normalizing Treatment and Galvanic Pack Carburizing Process on Mechanical Properties of Low Carbon Steel - Citra Wahyu Annisa; Ilyas Renreng; Lukamnul Hakim Arma; William Pian (EPI International Journal of Engineering, 2022)
Steel is the type of metal most often used in engineering. This study aimed to improve the mechanical properties of mild steel in terms of hardness, ductility, and other mechanical properties and to compare the hardness of carburized steel by galvanic treatment with non-galvanic carburizing of the steel. This research was carried out by varying the heat treatment process, namely carburizing with galvanic heat treatment and carburizing without galvanic, where the carburizing process uses activated carbon coconut shell charcoal with a weight percentage of 80% and 20% of K2CO3 (Potassium Carbonate) at a temperature of 9000C with a holding time of 60 minutes, 120 minutes and 180 minutes. The results obtained from this study indicate that the mechanical properties (hardness) of carbon steel increase at a temperature of 9000C with a holding time of 1 hour on the galvanic heating method with a better hardness value than the hardness of steel on the non-galvanic method. The hardness value obtained in the galvanic method is 94.06 HRB, while in the non-galvanic method, it is 76.4 HRB. And the pearlite phase is formed, increasing the hardness value on the surface of the specimen.